Efeito do tratamento com extrato etanólico de Aristolochia cymbifera sobre a regeneração nervosa periférica - Santos, Ana Cláudia Moreira dos (2019)
According to data from a study carried out at the Biotechnology Institute of the Uberlândia Federal University, the ethanolic extract of the Aristolochia cymbifera plant presented neuroprotective action in the Central Nervous System, protecting neurons from venom-induced death, and, acting positively on the epileptic crisis in sick flies. These data aroused the interest of testing the plant on the peripheral nerve regeneration, which is the subject of study in our laboratory. To do so, after the total left sciatic nerve of Wistar rats we used the tubulization technique, in which the nerve stumps are placed inside a silicone tubular prosthesis. During the two-month period the animals were evaluated for sensory and motor function of the nerve, the group treated with A. cymbifera was compared to a control group receiving placebo treatment. After these two months, the nerves were extracted for analysis of the behavior of Schwann cells (anti-S100beta and anti-NGFRp75 immunofluorescence, morphometry by light microscopy relative to myelination) and axonal growth (anti-neurofilament immunofluorescence; counting fiber by light microscopy). The functional or sensory results showed no difference between groups, as well as the immunoblotting, which did not show significant differences for the expression of the proteins studied. The morphometric analysis also showed no difference between the treated and control groups. There was a significant increase in myelin fibers for the nerves extracted from animals treated with the plant extract. Our data show that treatment with A. cymbifera may have little effect on the behavior of Schwann cells, however, the increase in number of myelin fibers may indicate a central protection in the microenvironment of the spinal cord in which the bodies of the neurons that had their axons injured. This idea is in accordance with previous results that already demonstrated a central neuroprotection of the plant.